Research on the Digital Preservation of Architectural Heritage Based on Virtual Reality Technology - Haohua Zheng; Leyang Chen; Hui Hu; Yihan Wang; Yangyang Wei (Buildings, 2024)
As a representative of the scientific and technological achievements of the new era, the overall development of virtual reality (VR) technology is becoming increasingly refined, which provides new development ideas and technical support in the field of ancient building restoration and architectural heritage preservation. In this context, digital conservation and the practice of architectural heritage have become important focuses of application in the industry. This paper starts from the core concept of VR technology, analyzes the value of the application of VR technology in the protection of ancient architecture, puts forward relevant suggestions and technical application methods, and takes Red Pagoda in Fuliang County as an example. In this sense, virtual reality technology is used to restore and protect the buildings, forming a digital heritage of ancient architecture. This study first utilizes a three-dimensional laser scanning instrument to collect point cloud data, and then the plane graph is drawn by measurement. Then, an Architectural Heritage Building Information Model is created, and comprehensive information on historical buildings is integrated. Finally, VR technology is used to show the effect of digital display and preservation. This study transforms architectural cultural heritage into a shareable and renewable digital form through restoration and reproduction, interpreting and utilizing it from a new perspective and providing new ideas and methods for architectural heritage conservation.